EFFECT OF SOIL - SOLARIZATION INTEGRATED WITH ORGANIC AMENDMENTS AND BIOAGENTS ON POPULATION DYNAMICS OF SOIL MICROBIAL POPULATIONS - ARORA, RUPESH KUMAR; SINGH, NIMISHA; ARORA, INDU (The Bioscan, 2013)
Soil-solarization, a hydrothermal process, is very simple, cheap and non hazardous technique, to cover airtight the moist soil with polyethylene mulches/sheeting during the period of intense solar radiations for the particular duration results in increases in the soil temperature. In the present investigations, plots for raising nurseries of vegetable crops were mulched with thin transparent polyethylene sheets for 8 weeks. During Solarization, the temperature on an average was 10 to 12°C higher than the unmulched soil. The plot (size-1m²) before mulching with transparent polythene sheets amended with organic amendments farm yard manure (2 kg/plot), poultry manure (2 kg/plot)) and bioagents Trichoderma harzianum (6 gm/plot), Pseudomonas fluorescens (6 gm/plot)) further increase soil’s suppressivity potential. The microbial population existing in soil was modified due to the hydrothermal process. Total populations of fungi, bacteria, actinomycetes, Trichoderma spp. except Pseudomonas fluorescens decreased drastically and significantly due to the solarization for 8 weeks. The microbial population (c.f.u) recorded in solarized plots just after soil-solarization of 8 weeks were as follows: fungi (13 to 27 × 10-3/ g soil), bacteria (40 to 61.23 × 10-6/g soil), actinomycetes (3.66 to 8.33 × 10-5/g soil) , Trichoderma spp. (15.44 to 28.22 × 10-3/g soil) and Pseudomonas fluorescens (52 to 68 × 10-6/g soil). In non-solarized plots, the population count (c.f.u) of fungi (31 to 56 × 10-3/g soil), bacteria (70 to 99.56 × 10-6/g soil), actinomycetes (6.83 to 13.33 × 10-5/g soil) and Trichoderma spp. (24.44 to 41.44 × 10-3/g soil) and Pseudomonas fluorescens (31.66 to 40.33 × 10-6/g soil). The microbiological changes of naturally existing populations of fungi, bacteria, actinomycetes, Trichoderma spp. were decreased and of P. fluorescens were increased by solarization carried out for 8 weeks. However, after 30 days i.e. after raising a nursery crop, the estimated population showed significant recovery except the population of P. fluorescens, changed only marginally.